Spatial Market Integration of Beef Cattle: A Vector Error Correction Model Analysis of Jakarta-NTT-Kalimantan Price Dynamics - Yusuf Fajar, Muhammad; Shaufi, Akhmad Raja (Bulletin of Applied Animal Research, 2026)
Spatial imbalances between beef production and consumption in Indonesia create inter-island trade dynamics that affect price transmission mechanisms across markets. This study aims to examine the long-run equilibrium relationships among beef prices in four regions, analyze the long-run and short-run dynamics and speed of price adjustment, and identify causality patterns and market hierarchy. The selected regions have distinct characteristics: DKI Jakarta as the consumption and import center, East Nusa Tenggara (NTT) as the production center, and South Kalimantan (Kalsel) and East Kalimantan (Kaltim) as deficit regions. Using daily price data from January 2021 to August 2024, the study employs Johansen cointegration test, Vector Error Correction Model (VECM), and Granger causality test. Results indicate that all four markets are fully cointegrated in the long run with four cointegrating vectors. The speed of price adjustment differs across regions, with NTT showing the fastest response (37.89% per day) and Jakarta the slowest (8.76% per day). Causality tests identify Jakarta as the leading market with significant influence on Kalsel, while NTT as a production center influences Jakarta, Kalsel, and Kaltim within the VECM framework. The causality pattern shows a market hierarchy of Jakarta-NTT-Kalsel/Kaltim, reflecting price information flow from the main consumer market to producers and deficit regions. Keywords: Market Integration, Beef Cattle, VECM, Price Transmission.